2017
DOI: 10.3363/prb.33.35
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Potassium-Substituted Hydroxyapatite Ceramics via Ultrasonic Spray-Pyrolysis Route

Abstract: Biological apatite presented in bone and teeth of mammals contains various ions, such as Na + , K + , Mg 2+ , F -and CO32-ions, in trace levels. Substitution of the above ions into hydroxyapatite (HAp) have great effect on the crystallinity, morphology, lattice parameters and stability of the apatite structure. It is known that potassium (K) in the living bone give a tremendous effect to the biomineralization process. Aim of this study is to clarify the influence of substitution of potassium into the HAp struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…Contraction of the lattice parameter "a" takes place as a result of the presence of these created additional hydroxide vacancies. However, another study reported increments in both lattice parameters with the addition of K [166]. Due to the higher ionic radius (1.33 Å), it might be expected that K + would prefer the Ca(2) site for substitution, but the experimental findings show the opposite trend [167].…”
Section: Monovalent Cationsmentioning
confidence: 97%
“…Contraction of the lattice parameter "a" takes place as a result of the presence of these created additional hydroxide vacancies. However, another study reported increments in both lattice parameters with the addition of K [166]. Due to the higher ionic radius (1.33 Å), it might be expected that K + would prefer the Ca(2) site for substitution, but the experimental findings show the opposite trend [167].…”
Section: Monovalent Cationsmentioning
confidence: 97%
“…In our previous study focused on cation doping, Yokota et al [9,10] fabricated sodium-or potassiumsubstituted HAp. They have also successfully fabricated bone HAp ceramics, including bone minerals with six types of ions; Na + , K + , Mg 2+ , F − , Cl − and CO 3 2− .…”
Section: Introductionmentioning
confidence: 99%
“…As described above, a number of studies have reported the effects of cations in biological apatite [3][4][5][6][7][8][9][10][11]. An artificially obtained material may have promoted bioactivity by the effect of substituted ions; for example, magnesium ions promote bone formation [14].…”
Section: Introductionmentioning
confidence: 99%
“…The calculation results by the least squares method listed in Table 1 showed a particular decrease for a parameter while c parameter was slightly varied. The a variation was governed by two antagonist effects: firstly, the substitution of K + (0.138 nm) for Ca 2+ (0.100 nm) induced an increase in the a values; however, as it was reported in the literature, the substitution of a divalent cation by a monovalent one decreased the channel diameter of a parameter and in consequence, a markedly decreased [28,29,31]. Secondly, the bibliography on hydroxfluorapatites reported that a parameter increased with a decreasing degree of fluoridation [36,37].…”
Section: Phase Analysismentioning
confidence: 64%
“…Moreover, potassium is indispensable for bone nucleation and biomineralization processes [27]. The literature reports have revealed that doping by potassium has occurred without any significant effects on the structural stability of apatites, and that ~20 atom.% were introduced into the apatite structure [28][29][30]. Meanwhile, lattice parameters slightly decreased when the level of substituted K + increased.…”
Section: Introductionmentioning
confidence: 99%